2010
DOI: 10.1002/cncr.2820360608
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-induced myocardial infarction

Abstract: A patient with lymphosarcoma treated with weekly injections of vincristine developed an acute myocardial infarction immediately after the second injection of vincristine. After he recovered from the infarction, the treatment was continued and he developed an additional myocardial infarction. I n vivo and in vitro studies have not revealed any effect of vincristine on the clotting mechanism. T h e possible causes for the association of vincristine-treated lymphoma and myocardial infarction are discussed.Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Series that compare incidental cardiac disease in lymphoma patients treated with anthracyclines to the similar risk in a matched background population could potentially overestimate the cardiotoxic effects of anthracyclines because lymphoma in general, as well as surveillance bias arising from being frequently consulted by physicians, may be associated with cardiotoxicity and increased likelihood of being diagnosed with CVD. Of note, other drugs included in the R‐CHOP regimen such as rituximab, cyclophosphamide and vincristine, have been causally linked to cardiotoxicity (Mandel et al , ; Mills & Roberts, ; Gottdiener et al , ; Goldberg et al , ; Foran et al , ; Renard et al , ). In this Danish nationwide study, we examined the risk of cardiac disease (CHF and CVD) in a cohort of patients with DLBCL or follicular lymphoma (FL) treated with immunochemotherapy with or without anthracyclines in first‐line.…”
mentioning
confidence: 99%
“…Series that compare incidental cardiac disease in lymphoma patients treated with anthracyclines to the similar risk in a matched background population could potentially overestimate the cardiotoxic effects of anthracyclines because lymphoma in general, as well as surveillance bias arising from being frequently consulted by physicians, may be associated with cardiotoxicity and increased likelihood of being diagnosed with CVD. Of note, other drugs included in the R‐CHOP regimen such as rituximab, cyclophosphamide and vincristine, have been causally linked to cardiotoxicity (Mandel et al , ; Mills & Roberts, ; Gottdiener et al , ; Goldberg et al , ; Foran et al , ; Renard et al , ). In this Danish nationwide study, we examined the risk of cardiac disease (CHF and CVD) in a cohort of patients with DLBCL or follicular lymphoma (FL) treated with immunochemotherapy with or without anthracyclines in first‐line.…”
mentioning
confidence: 99%
“…2,6,7 A study by Mikaelian and colleagues 8 showed that tubulin-binding drugs (including vincristine and vinblastine) can induce cell-cycle arrest of the rapidly proliferating cardiac endothelial cells and cause myocardial infarction. Vincristine is more often reported to cause ischemic syndromes than is rituximab, but a catastrophic synergism of vincristine and rituximab certainly cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise complications have been reported with capecitabine, an orally administered prodrug of 5-FU [15]. Furthermore, coronary vasospasm and myocardial ischemia have been linked to vinca alkaloids (e.g., vincristine, vinblastine) [16,17].…”
Section: Effects Of Oncological Treatment On the Pathogenesis Of Cardmentioning
confidence: 99%